2014
DOI: 10.1016/j.molmet.2014.01.005
|View full text |Cite
|
Sign up to set email alerts
|

Adipokines – removing road blocks to obesity and diabetes therapy

Abstract: Prevention of obesity and therapeutic weight loss interventions have provided only limited long term success. Therefore there is an urgent need to develop novel pharmacological treatment strategies, which target mechanisms underlying positive energy balance, excessive fat accumulation and adverse fat distribution. Adipokines may have potential for future pharmacological treatment strategies of obesity and metabolic diseases, because they are involved in the regulation of appetite and satiety, energy expenditur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
184
1
19

Year Published

2015
2015
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 232 publications
(207 citation statements)
references
References 99 publications
(133 reference statements)
3
184
1
19
Order By: Relevance
“…Levels of the adipokines leptin and adiponectin, which are considered to be therapeutic targets/tools in obesity (24), were also observed to be affected by these compounds. In our study, acarbose was found to increase adiponectin levels in the treated obese rats, which is in accordance with previous reports concerning diabetic patients (25) and diabetic obese rats (26).…”
Section: Discussionmentioning
confidence: 99%
“…Levels of the adipokines leptin and adiponectin, which are considered to be therapeutic targets/tools in obesity (24), were also observed to be affected by these compounds. In our study, acarbose was found to increase adiponectin levels in the treated obese rats, which is in accordance with previous reports concerning diabetic patients (25) and diabetic obese rats (26).…”
Section: Discussionmentioning
confidence: 99%
“…However, in recent years researchers have demonstrated that a multi-therapy of leptin in combination with other leptin sensitisers may be able to improve peripheral leptin sensitivity and may hold therapeutic promise (Moon et al, 2011;Müller et al, 2012;Matthias, 2014;Crujeiras et al, 2015;Park & Ahima, 2015). These leptin sensitisers target distinct neuroendocrine systems related to leptin signalling pathology.…”
Section: Multi-therapy Of Leptinmentioning
confidence: 99%
“…Nevertheless, overcoming resistance to the leptin therapy continues to challenge the researchers. In recent years some preclinical studies have surprisingly demonstrated that resistance to leptin can be reversed and the effects of leptin therapy can be amplified by several leptin sensitisers (Moon et al, 2011;Müller et al, 2012;Matthias, 2014;Crujeiras et al, 2015;Park & Ahima, 2015). Accordingly, it is the aim of this paper to critically discuss the plausible revival of leptin for obesity therapy with reference to research findings on various influencing factors contributing to the level of expression and secretion of leptin.…”
Section: Introductionmentioning
confidence: 99%
“…El exceso o déficit del TA resultará en una producción o liberación alterada de los mediadores antes mencionados, ocasionando una comunicación defectuosa con otros órganos, alteraciones en el metabolismo y el desarrollo posterior de enfermedades endocrino-metabólicas. Un exceso de TA en la región visceral se ha asociado con insulino resistina, variables de dimensión y composición corporal -A. souki et al rev Med chile 2016; 144: 307-316 resistencia (IR), DM2, dislipidemia, hiperglicemia e hipertensión, así como estados protrombóticos y proinflamatorios [4][5][6] .…”
unclassified